Praktik Prostitusi Pada Profesi 'Sales Promotion Girl' di Kota Malang - Tery Ayudia Dianita (Sociology Department, Brawijaya University, 2023)
Sales Promotion Girl (SPG) chooses to become a Commercial Sex Worker (Hookers) with reason. In the process of choosing a side job, lifestyle, daily needs, and paying debts/installments play an important role. This study aims to reveal the rational choice of Sales Promotion Girls (SPG) who make themselves Commercial Sex Workers (Hookers) outside working hours. The research design is a qualitative interpretive with a case study approach. Data was collected through observation and in-depth interviews with 5 (five) informants who chose side jobs as Commercial Sex Workers (Hookers). Researchers use James S. Coleman's rational choice theory to explain this phenomenon by looking at the aspects of resources, collective behavior, sacrifices, and rewards. The data processing technique uses the case study data analysis method. Lincoln and Guba (1985) state that a case study is an in-depth and detailed study of everything related to the research subject. The results of this study indicate that the rational choice of a Sales Promotion Girl (SPG) who chooses to become a Commercial Sex Worker (Hookers) is more influenced by life's problems and the need for life values than mere material desires. Keywords: Sales Promotion Girl (SPG); Commercial Sex Workers (Hookers); Rational Choice